Investigation of the transport and absorption of Angelica sinensis polysaccharide through gastrointestinal tract both in vitro and in vivo. (1st January 2017) - Wang, Kaiping; Cheng, Fang; Pan, Xianglin; Zhou, Tao; Liu, Xiqiu; Zheng, Ziming; Luo, Li; Zhang, Yu
Abstract: To investigate the absorption and delivery of ASP in gastrointestinal (GI) tract, cASP was successfully synthesized by chemically modifying with succinic anhydride and then conjugating with a near infrared fluorescent dye Cy5.5. Then, the capacity of oral absorption of cASP was evaluated. The results demonstrated that cASP had low toxicity and no disruption on the integrity of cell membrane. The endocytosis of cASP into the epithelial cells was time- and energy-dependent, which was mediated by macropinocytosis pathway and clathrin- and caveolae (or lipid raft)-related routes. Otherwise, the actin filaments played a relatively weak role at the same time. The transport study illustrated that cASP could penetrate through the epithelial monolayer and mainly mediated by the same routes as that in the endocytosis experiment. Moreover, both in vitro Ussing chamber and in vivo ligated intestinal loops models indicated that cASP could be diffused through the mucus barriers and be absorbed in the whole small intestine. Finally, near-infrared fluorescence imaging presented that cASP could be absorbed and circulated into the blood, then distributed into various organs after oral administration. In conclusion, ASP could be absorbed after oral administration through endocytosis process mainly mediated by macropinocytosis pathway and clathrin- and caveolae (or lipid raft)-related routes, then be absorbed and circulated into blood. This study presents a comprehensive understanding of oral delivery of cASP, which will provide theoretical basis for the clinical application of ASP.